IRIS MURDOCH'S NOVEL "A SEVERED HEAD": CRIME, REALITY, AND ETHICS - Ahlam Dhahir Mohsin Al-Shamarti; Ghaith Saleh Mahdi (American Journals, 2023)
Interesting points about "A Severed Head" are discussed in this study. The author's fascinating approach, rife with symbols, philosophical and psychological features, makes for a compelling read that leaves readers in awe. There is a strong interdependence between the characters, which forms a chain of events leading to revelations of truth, provocation of reactions, exposure of secrets, confrontation, breakups, and new relationships. In this context, "crime" does not refer to a specific offense category but to any action that endangers another person's well-being. Everyone seeks the truth, but it's notoriously elusive. Morality is examined in opposition to its antithesis, immorality. The author does not offer cookie-cutter answers to the problems. The ending is vague enough to be susceptible to various interpretations. Everything about this novel is postmodern.